Aristotle, Martin, and Grube: “Ajaws”, “Kings”, “Reges”, and the Unified Theory of Politics - Christopher Binetti (Britain International for Academic Research (BIAR-Publisher), 2024)
This paper applies the new concept of the Unified Theory of Politics, which states that any polity with writing can be compared with any other polity with writing, regardless of culture, place, and time. In this paper, we will look at political terms for rulers, particularly those for monarchs, in order both to compare them and to correct equivalences that do not make sense. The most distinct Civilization in the world is Mesoamerica. Its most well-known literate civilization is the Mayan civilization. Martin and Grube are the experts on the political institutions of the Classic Mayans. They are, in fact, the ones who best show the ability to compare Mayan monarchy to other monarchies from across the world. However, they mistranslate a key term, which is the core problem that this paper attempts to solve. Martin and Grube translate “ajaw” and its variants as “king”. The title for a stronger ruler, “kaloomte” and its variants, does not seem to be translated into a particular term by Martin and Grube. Their book is by far the most thorough look at Mayan political regimes, offices, and titles, though Coe and Houston also have something to say about this. The equation of “ajaw” with “king” seems to be uncontested. In order to compare rulers from different cultures, times, and places as the Unified Theory of Politics demands, we need analytically-comparable terms. In this paper, it will be argued that an “ajaw” is not “king”. Instead, an “ajaw” can be described as a legitimate ruler, a sovereign, or a monarch. In working towards this conclusion, this paper will argue that the term “king” should be used sparingly in historical-comparative studies and if possible, in common parlance. Not only is “ajaw” an inappropriate synonym for “king”, but even the term “rex”, which is usually translated as if unproblematic as “king” really should not be so translated. This is true essentially down the line of common equations with “king”. Some of these equations are comparable but never really equate to “king”. This paper uses Aristotle and the Unified Theory Politics to come up with a political taxonomy of monarchies that not only resolves the above problem, but allows for cross-cultural analysis of thirty-seven distinct monarchical offices.